(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The incidence of vitreous hemorrhage after vitrectomy for proliferative diabetic retinopathy (PDR) has been reported to vary from 21% to 80%. Purpose: To assess the efficacy of gas exchange tamponade (GET) in combination with intravitreal aflibercept for post-vitrectomy vitreous hemorrhage in patients with PDR. Material and Methods: We reviewed the medical records of 47 patients (47 eyes) who developed vitreous hemorrhage after vitrectomy for PDR and received a 20% C3F8 GET in combination with 2.0-mg intravitreal aflibercept (EYLEA®). Results: At 2 months, examination showed “transparent” vitreous cavity in 43 eyes (91.5%), and vitreous hemorrhage was still present in other 4 eyes (8.6%), including a recurrence in 2 eyes (4.3%). At 6 months, examination showed “transparent” vitreous cavity in 46 eyes (97.9%), and only one eye (2.1%) developed a recurrence of vitreous hemorrhage within two months to six months after primary surgery. At the 2 month follow-up, visual acuity was 0.1 to 0.3 in 24 eyes (51%), better than 0.35 in 17 eyes (36.2%), and lower than 0.1 in only 6 eyes (12.8%). At the 6 month follow-up, visual acuity remained similar to that at month 2, but the number of eyes with visual acuity better than 0.35 increased from 17 to 19. Conclusion: A 20% C3F8 GET in combination with intravitreal aflibercept is an effective method of treatment for vitreous hemorrhage after vitrectomy in patients with PDR and may be widely used in practice.